Spray-printed magnetoelectric multifunctional composites - Martins, Pedro Libânio Abreu (2020)
The performance of spray-printed magnetoelectric (ME) composites based on poly (vinylidene fluoride-co-trifluoroethylene)/cobalt ferrite, P(VDF-TrFE)/CoFe2O4, is reported and discussed. Spray-printing has been chosen as a production technique since it is a transformative approach to industrial production. With the addition of 20 wt% of ferrite content, the resulting composite exhibits a fibrillar-porous structure, an ≈1.8 GPa Young's Modulus, a saturation magnetization of 11.2 emu. g−1, a 6.0 emu. g−1 magnetic remanence and a magnetic coercivity of 2050 Oe. The high dielectric (34 dielectric constant at 10 kHz) and piezoelectric (−27 pC.N−1) responses explain the high ME coupling of 21.2 mV cm−1 Oe−1 at an optimum magnetic field of 2450 Oe. The high ME response and the simple/scalable additive manufacturing method demonstrates the suitability of these materials for cost-effective and large-scale sensor/actuator applications, namely in aerospace, automotive and recreational products